ACCOUNTABILITY OF PUBLIC OFFICIALS FROM THE PERSPECTIVE OF ADMINISTRATIVE LAW: PREVENTING MALADMINISTRATION IN PUBLIC SERVICE DELIVERY - Novi Juli Rosani Zulkarnain; Mohammad Reevany Bustami (Institut Riset dan Pengembangan Indonesia, 2026)
This study aims to analyze the accountability of public officials from the perspective of state administrative law as an effort to prevent maladministration in public services in Medan City, North Sumatra. Public accountability is important because public officials exercise administrative authority that directly affects citizens’ rights, access to services, and trust in government institutions. This study uses a normative-empirical legal research method. The normative approach is applied by examining laws, regulations, legal principles, and doctrines related to public service accountability, while the empirical approach is used to understand the implementation of accountability in public service practices. The findings show that maladministration is often related to weak procedural compliance, limited transparency, ineffective complaint handling, weak supervision, institutional constraints, and low public legal awareness. The study also finds that the principles of legality, transparency, equality, carefulness, responsiveness, and public interest are essential in strengthening administrative accountability. In conclusion, the prevention of maladministration in Medan City requires the strengthening of service standards, transparent procedures, effective complaint mechanisms, internal and external supervision, institutional capacity, digital public services, and public legal awareness. Public official accountability should not only function as a form of responsibility after violations occur, but also as a preventive legal mechanism to ensure fair, responsive, and accountable public services.